Unveiling the relationship between the use of open educational resources and the adoption of open teaching practices in higher education - Nascimbeni, Fabio; Burgos, Daniel (Sustainability (Switzerland), 2020)
The goal of this paper is to advance the understanding of the way university educators currently adopt open educational practices (OEP) by analyzing the relation between the use of open educational resources (OER) and the implementation of open teaching practices. The results are based on data collected through an online survey among 724 university educators. Depending on the actual use of OER and open teaching practices by the survey respondents, we have categorized them along a scale that goes from “novice” to “expert”, and we analyzed the data to evaluate their use of OER and their adoption of open teaching practices, looking for relationships between the two phenomena. The main finding of this paper, which confirms the latest research findings from the open education community, is that a strong relationship exists between the two dimensions: The more an educator uses OER, the more he will probably adopt open teaching practices, and vice versa. These results are discussed with a view to use this virtuous circle between the use of open content and adoption of open teaching as a way to build generalized open education capacity among universities’ teaching staf
Keywords: open educational resources; open teaching practices; higher education; Scopus; JCR